2017
DOI: 10.5851/kosfa.2017.37.2.242
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidative Activity of Various Levels of Ethanol Extracted Tomato Powder and Application to Pork Patties

Abstract: This study was performed to evaluate antioxidant activity of tomato powder extracted by various concentrations of ethanol (0, 25, 50, 75, 100%) and to evaluate the physicochemical properties and antioxidant activities of pork patties with ethanol extracted tomato (EET) powder. No differences in the contents of total of individual phenolic compounds including gallic acid and catechin, were observed among the treatments (p>0.05). Among the various concentrations, 50% and 75% EET powder showed the highest free ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
(51 reference statements)
1
9
0
Order By: Relevance
“…Other studies reported Chlorogenic acid and Rutin as the major phenolic compounds in tomatoes (Scarano et al, 2020). Gallic acid (36.0 to 47.6 mg/100 g) and Catechin (49.3 to 61.7 mg/100 g) were reported in tomato powder, too (Kim & Chin, 2017). Integrating the previous results with ours, we concluded that the major compounds released in response to thermal stress were found to change.…”
Section: Discussionsupporting
confidence: 82%
“…Other studies reported Chlorogenic acid and Rutin as the major phenolic compounds in tomatoes (Scarano et al, 2020). Gallic acid (36.0 to 47.6 mg/100 g) and Catechin (49.3 to 61.7 mg/100 g) were reported in tomato powder, too (Kim & Chin, 2017). Integrating the previous results with ours, we concluded that the major compounds released in response to thermal stress were found to change.…”
Section: Discussionsupporting
confidence: 82%
“…In general, wine lees addition did not affect TVC (p > 0.05). In this sense, other natural extracts (chestnut and seaweed) did not influenced TVC throughout storage, while tea and grape extracts and tomato powder led to a decrease in pork burgers [23,27]. Furthermore, it was observed that chilled storage caused a progressive increase (p < 0.001) in psychotrophic aerobic bacteria counts, especially in control burgers, reaching values of 8 log CFU/g, while burgers with lees kept the initial counts during the first eight days of storage (5.7-6.5 log CFU/g).…”
Section: Microbiological Quantificationmentioning
confidence: 93%
“…For instance, the work of Freitas et al [76] used a system mostly composed of ethanol, which might allow the LPIP determination of a wider range of NPs (including some less polar extracts) using water-soluble radical initiators (such as AAPH) or transition metals. In more aqueous systems, the use of saponified linoleic acid (the sodium salt, for instance) to increase water solubility, with [70,73,128] or without [70,126] the addition of a surfactant, might be a solution to test very hydrophilic compounds (such as natural polysaccharides), which are insoluble, even at low concentrations of organic solvents.…”
Section: Watermentioning
confidence: 99%